THE IMPACT OF THE GIG ECONOMY ON FAMILY STRUCTURE AND SOCIAL RELATIONS IN URBAN AREAS - Komarudin, Komarudin; Magfiroh, Diana (Advances In Social Humanities Research, 2023)
The development of the digital economy has encouraged the emergence of the gig economy as a new form of work relationships in urban areas. Platform-based jobs offer additional time flexibility and earning opportunities, but on the other hand they also present uncertainty and pressures that affect the social lives of their workers. This study aims to analyze the impact of the gig economy on family structure and social relations in urban environments, focusing on the Indonesian context. Using an exploratory qualitative approach, data was collected through in-depth interviews and participatory observations of gig workers from various platforms, as well as their family members. The results show that gig work leads to a shift in domestic roles, a decrease in the quality of family interactions, and role conflicts due to unclear work boundaries. Additionally, gig workers tend to experience decreased participation in community activities, leading to social isolation and reduced social cohesion in the residential environment. This study confirms that the impact of the gig economy is not only economic, but also social and structural, so there is a need for policy interventions that support social protection and work-life balance for urban gig workers.